Investigation of thiolysis of 4-substituted SBD derivatives and rational design of a GSH-selective fluorescent probe. Issue 29 (13th July 2021) - Yang, Chao; Tu, Xiaoqiang; Ji, Xiuru; Ye, Haishun; Li, Shan; Sun, Lu; Yi, Long; Xi, Zhen
Abstract : 4-Substituted SBD derivatives are tunable structural motifs for thiol-mediated thiolysis reactions, and a new GSH-selective receptor is designed for dual-functional fluorescent probes. Abstract : In order to evaluate 7-sulfonamide benzoxadiazole (SBD) derivatives for the development of fluorescent probes, herein we investigated the thiolysis reactivity and selectivity of a series of SBD compounds with different atoms (N/O/S/Se) at the 4-position. Both SBD-amine and SBD-ether are stable toward biothiols in buffer (pH 7.4), while SBD-selenoether can react efficiently with biothiols GSH/Hcy, Cys, and H2 S to produce SBD-SG/S-Hcy, SBD-NH-Cys, and SBD-SH, respectively, with three different sets of spectral signals. Therefore, the SBD-selenoether compounds should be useful platforms for the differentiation of these biothiols. Though SBD-alkylthioether shows much lower reactivity than SBD-selenoether, SBD-arylthioether is a tunable motif and structural modifications at the aryl moiety enable the rate of thiol-mediated thiolysis to be modified. To this end, an ER-targeted GSH-selective fluorescent probe 7 was rationally designed via thiolysis of SBD-arylthioether. Compared with control probe SBD-Cl, probe 7 exhibits improved GSH selectivity and better biocompatibility. In total, this study highlights that the modification at the 4-position of SBD is an efficient strategy for the development of new fluorescent probes with tunable reactivity and selectivity.